A Review of the Accuracy of Crash Coding When Applied to Motorcycle Crashes - Liz de Rome; Christopher Hurren; Thomas Brandon (Journal of Road Safety)
The coding of road crashes is designed to identify patterns of contributing factors for the development of countermeasures. In Australia, crash type is defined by the last vehicle movement before the first crash impact. This coding system was originally based on police data for motor vehicle crashes but did not distinguish between vehicle types. The aim of this study was to examine the accuracy of current crash coding practice when applied to motorcycle crashes. This was a population-based study of 1,479 motorcycle crashes reported in Tasmania between 2013-2016. All crashes were recoded based on details from police reports and the revised codes were compared to those assigned by the road authority. The defining role of the last vehicle movement was suspended in cases where it excluded other prior contributing factors identified in the police report. Almost half of the motorcycle crashes were reclassified to incorporate additional information from the police reports including contributing factors or prior events that are characteristic of motorcycle crashes. These factors had been excluded in the original coding due to the last vehicle movement protocol. The last vehicle movement is not an appropriate method for classifying motorcycle crashes. Training in crash reporting for police and road authorities should include awareness of the different contributing crash factors for different vehicle types and the importance of accurate crash data for the development of targeted countermeasures. The addition of motorcycle specific crash categories and subcodes to the coding systems is also recommended.